Implementation of Minimum Service Standards (MSS) Policies on Non-Communicable Diseases (NCD): A Literature Review - Gigih Gunawan; Katmini (Journal for Quality in Public Health, 2022)
The occurrence of epidemiological transitions, demographics, nutritional transitions and the transition of community behavior is the cause of the continued increase in cases of non-communicable diseases (NCDs). So it is very important to intervene through policies as an effort to prevent and control NCDs. Countries around the world have adopted WHO-PEN which is the basis for making relevant policies in the form of Minimum Service Standards (MSS) for Non-Communicable Diseases provided at primary health care facilities. This study intends to look at the implementation of the policy and see the obstacles faced in the implementation. The method used in this research is literature review, research data is taken through the wiley online library database, google schooler, proquest, pubmed and researchgate using the Preferre Reporting Items for Systematic Reviews and Meta Analysis method using the keywords public health and minimum service standards and non-communicable diseases. With the exclusion criteria, the articles below were published under 2015, incomplete presentation, articles not discussing minimum service standards, non-communicable diseases and health policies. The results show that the key policies adopted by various countries in designing and providing health services refer to WHO-PEN which is adapted to the conditions of the local community centered on three important components of health promotion as prevention efforts by controlling NCDs risk factors and carrying out adequate treatment at health facilities. The base is the health center. NCDs minimum service standards includes; availability of human resources that handle NCDs, availability of medical equipment for handling NCDs, control of NCDs risk factors, availability of drugs for NCDs, running of NCDs programe activities. However, most of the community health centers could not achieve the target of 100 percent of the NCDs minimum service standart target. This is due to 1) standard constraints and policy objectives; (2) resource constraints; (3) constraints on the characteristics of implementing organizations; (4) communication barriers between implementing organizations; (5) constraints on the attitude of the implementers; (6) the constraints of the social environment of the community.